ANALISIS PENDAPATAN DAN FUNGSI PRODUKSI RUMPUT LAUT (Gracilaria sp.) DI KECAMATAN JABON KABUPATEN SIDOARJO - Dwipriyono, Yoga; Indah, Pawana Nur; Sudiyarto, Sudiyarto (Berkala Ilmiah AGRIDEVINA, 2020)
Small islands in Indonesia have prospects for seaweed development. Therefore, it is necessary to calculate how many income and production function of seaweed Gracilaria sp. cultivation in order to know wheter the cultivation is profitable or not and how many profit is obtained by the pond farmers. This research aims to : 1) Determine and analyze the level of farmers’s income in seaweed Gracilaria sp. cultivation; 2) Determine the factors that affect seaweed Gracilaria sp. production; and 3) Determine and analyze how efficient use of planting area, seeds, labor, and harvest time on seaweed Gracilaria sp.  cultivation production. The research was conducted in Tanjung Sari hamlet, Jabon sub-district, Sidoarjo regency, East Java. Data collection methods used are interview methods, questionnaires, observation and documentation. The analysis used in this research is income analysis, Cobb-Douglas analysis and efficiency analysis. The results showed that the income level of pond farmers in the production of seaweed Gracilaria sp. was profitable and feasible to cultivate, partially had a positive effect on seaweed Gracilaria sp.  production and overall the variables had a positive effect on variable Y, namely seaweed Gracilaria sp.  production, and efficiency in seaweed Gracilaria sp. farming had a combination of inputs that were not optimum. DOI : https://doi.org/10.33005/adv.v9i2.2461